Interprofessional education and service learning: a model for the future of health professions education. Issue 4 (July 2014) - De Los Santos, Maria; McFarlin, Christine Degnon; Martin, Lourdes
Abstract The implementation of interprofessional education for healthcare professionals has been lackluster, at best, since it was recommended by the Institute of Medicine. There have been various attempts in institutions of higher learning to meet this goal with mixed results. Herbert Wertheim College of Medicine, Florida International University has developed the Green Family NeighborhoodHELP™ (GFNHelp) program to meet this challenge. GFNHelp is an interprofessional, longitudinal, service-learning program for healthcare students. Through participation in this program medical students team up with students from other professions, such as nursing, social work, and law, and collaborate to improve health outcomes for medically underserved families in the community. This educational program emphasizes the Core Competencies of the Interprofessional Education Collaborative through community-based service-learning, allowing student teams to engage firsthand and address the impact of social determinants on health.